Proposed Industry 4.0 architecture in the supply chain from the perspective of industrial engineering (2017)
Introduction: This article derives from the research into big data applications, conducted at the Universidad Distrital Francisco José de Caldas in 2017, which seeks to solve the problem of compatibility between the information generated by sensors in equipment and machines, and the platforms that support such information. A proposed architecture that can be adopted by supply chains immersed in Industry 4.0 is shown. The elements, authors, and stakeholders that interact in the architecture were identified. Methodology: a) the importance of Industry 4.0 is argued; b) it is stated that organizations must adapt to the new industrial revolution; c) the research literature is reviewed. These findings are methodically analyzed for proposals, advances, methodology, future research, results and conclusions; d) an architecture is proposed; e) a mobile application is created to evaluate the interconnection of the sensor layer with the application layer proposed by the architecture; f) the usability of the application is checked; and g) the advantages and limitations of the architecture are explained. Results: The application has a 91 % usability allowing real-time connection between the sensor layer and the application layer. Conclusions: This research presents tools that provide the supply chain with guidelines to be included in Industry 4.0 and to obtain competitive advantages.